Receptive Program of Understanding Reader - Lyudmila Ivanovna Strelets (Филологический класс, 2013)
The article deals with the type of understanding the reader of the artworks and the structure of his receptive program, which is based on the position of the ability of the text to contain a strategy for reading and perception. The author proposes to create a portrait of an imaginary reader in the mind of the real reader. A methodological solution of this problem is shown by comparing poems of Anna Akhmatova and Marina Tsvetaeva in the lesson “And every reader as the mystery...”.